Protein availability of an instant drink in base of plantain (Musa Paradisiaca L.) and guandul (Cajanus cajan (L.) Millsp) meal - Godoy Bonilla, Sandra Patricia; Lemos Materón, Cindy; López Gómez, Astrid Yobana (Revista Colombiana de Investigaciones Agroindustriales, 2016)
This research succeeded in developing a protein-energy instant drink, from banana variety Dominican (Musa paradisiaca L.), pigeon pea (Cajanus cajan (L.) Millsp) meal enriched. This latter being an important source of protein further provides trace elements such as iron, calcium, copper, phosphorus and manganese. Methodological development inclusions were made 20, 25 and 30% pigeon pea flour, establishing protein intake in composite flours by the Kjeldahl method, besides thermal properties were determined (viscosity, pasting temperature) and functional properties (index absorption rate of solubility and swelling power) in the instant beverage. It was possible to enrich plantain flour (α≤ 0.05%) with 30% pigeon pea flour. The drink showed a water absorption rate of 3.5 g water.g-1 of starch, water solubility index of 23.56 g.100g-1 sample bs and swelling power of 4.6 g gel / g starch, flour eigenvalues unconventional due to: high carbohydrate content (84.07%), dietary fiber (6.59%) and protein (7.08%) variability in the size of the starch granule and high gelatinization temperature reached 80° C for 10 minutes in plantain meal and 87° C for 30 minutes in pigeon pea meal. Para citar este artículo Godoy, S., Lemos, C. y López, A. (2016). Disponibilidad proteica de una bebida instantánea a partir de harina de plátano (Musa paradisiaca L.) y guandúl (Cajanus cajan (L.) Millsp). Rev. Colomb. Investig. Agroindustriales, 3(1), 76-82. DOI: https://doi.org/10.23850/24220582.344